Development of a Website-Based Online Rice Bowl Ordering System Using Agile Methods for Culinary_bykiki UMKM - Syahputra, Tengku Deandra (Journal of Technology and Computer, 2025)
The development of information technology has encouraged Micro, Small and Medium Enterprises (MSMEs) to adapt in managing their businesses more efficiently and competitively. One of the main challenges for culinary MSMEs is the limitation of manual ordering systems, which often leads to issues such as service delays, mistakes in order recording, and suboptimal product promotion. This study aims to design and build a web-based rice bowl ordering system that can facilitate the transaction process between consumers and business actors. The development method used is Agile, due to its iterative and flexible nature, as well as its ability to dynamically adjust to user needs. The research process includes needs analysis, system design, and testing stages. The results of the study indicate that the developed system can enhance the efficiency of order management, expand marketing reach, and provide an experience better users. Thus, this system is expected to be an innovative solution for culinary SMEs in facing competition in the digital era.